Disaggregate level simulation of bus transit emissions in a large urban region. Issue 7 (2nd July 2020) - Waraich, Asad Shahbaz; Anowar, Sabreena; Tenaglia, Tristano; Sider, Timothy; Alam, Ahsan; Minaei, Negaar Shabaanzaadeh; Hatzopoulou, Marianne; Eluru, Naveen
Abstract: In this study, we demonstrate the development of a methodology for simulating transit bus ridership and greenhouse gas emissions (in CO2 equivalent) across a network of 200 bus lines in the city of Montreal, Canada. The current study estimates ridership and emissions at a micro level, that is, at the disaggregate stop level for 24 h of a typical weekday for all the bus lines (and their trips) in the bus network of Montreal. The disaggregate level simulation process incorporates for specificities such as vehicle type, age, fuel, and passenger load. The micro-simulation platform developed has three embedded modules: (1) stop level boarding and alighting, (2) bus occupancy determination, and (3) disaggregate emission estimation. Our simulation allows us to estimate emissions for individual buses while running as well as while idling at bus stops. The proposed model system provides measures of per capita emissions (total emissions/total boardings), per km emissions (total emissions/total kilometers traveled), and per person km emissions (total emissions/total person kilometers traveled on bus transit). To further illustrate the applicability of the proposed study, we conducted several policy scenario analyses. We investigated the effect of a 20% system-wide increase in ridership and observed a 1.1% increase in total emissions and a 13% decrease in per capita emissions. We estimated the effects of decreasing the frequency of low occupancy buses and increasing the frequency of high occupancy buses as well and observed that these frequency changes are associated with proportional changes in emissions.